PEREMPUAN DAN POLITIK: MEMBANGUN KESADARAN HUKUM PEMILIH PEREMPUAN DALAM PENGGUNAAN HAK SUARA MENJELANG PEMILU 2024 - Harun, Rina Rohayu; Erwin, Yulias; Septyanun, Nurjannah; Supryadi, Ady; Yamin, Bahri; Fahrurrozi, Fahrurrozi; Yuliani, Tin (JCES (Journal of Character Education Society), 2023)
Abstrak : Pesta demokrasi yang kita kenal dengan Pemilihan Umum (Pemilu) di negera kita, diselenggarakan setiap 5 (lima) tahun sekali. Fenomena yang terjadi saat ini, masih banyak pemilih khususnya perempuan, yang apatis dalam penggunaan hak suaranya. Oleh karena itu tujuan kegiatan ini adalah, memberikan pemahaman kepada pemilih perempuan, pada anggota Yayasan Perempuan Berdaya Lombok NTB. Kegiatan ini telah diikuti oleh oleh anggota Yayasan sebanyak 25 orang. Tahap awal dari kegiatan ini, masyarakat perempuan diberikan trik dalam mengkualifikasikan calon yang layak untuk dipilih, tahap akhir sesi diskusi dan evaluasi dengan menggunakan angket manual. Hasil kegiatan menunjukkan 80% peserta memahami materi yang sampaikan. Harapan dengan adanya materi, diskusi dan informasi yang diperoleh oleh pemilih perempuan dari kegiatan ini, dapat diaplikasikan untuk pemilu 2024 dan seterusnya. Abstract: Tuli The democratic party that we know as general elections (elections) in our country is held every 5 (five) years. Elections require the support of all parties, including voters because what determines the elected candidates is the people's vote/suffrage from members of the public. The current phenomenon is that there are still many voters, especially women, who are apathetic about exercising their voting rights. Therefore the purpose of this activity is to provide understanding to women voters, and members of the Empowered Women's Foundation in Lombok, NTB. This activity was attended by 25 members of the Foundation. In the early stages of this activity, women's communities were given tricks in qualifying candidates who were eligible to be elected, based on aspects of piety, integrity, track record of caring and contribution (not just material things, but also ideas and enthusiasm to build the community). The results of the activity show that women voters in Perampuan Village are still apathetic in exercising their voting rights. It is hoped that the material and information obtained by female voters from this activity, it can shift the mindset of female voters, regarding the importance of women's voices in the upcoming 2024 election.